Studi Analisis Terhadap Faktor-Faktor yang Mempengaruhi Persistensi Laba pada Perusahaan (Kasus Perusahaan Manufaktur di Indonesia Periode 2021–2023) - Wijayanto, Kusuma; Juliansyah, Athira; Apriliya, Fivit (JAB (Jurnal Akuntansi & Bisnis), 2025)
The Covid-19 pandemic is a problem that occurs in all industries around the world, including Indonesia. Companies are asked to recover from the Covid-19 pandemic by providing stable Company profit performance for the benefit of stakeholders. Many studies have conducted research related to the persistence of Company profits during and before the pandemic. Considering this, this study uses a different perspective, namely taking the research time after the Covid-19 pandemic. This study examines the relationship between institutional ownership, managerial ownership, independent board of commissioners, audit committee and book tax difference with the persistence of Company profits. This study uses a sample of manufacturing sector companies listed on the Indonesia Stock Exchange in 2020 to 2022. The findings of the results of this research test are that institutional ownership and managerial ownership do not affect the persistence of Company profits after the pandemic. Independent board of commissioners, audit committee and book tax difference affect the persistence of Company profits after the pandemic.